2013
DOI: 10.1176/appi.ps.201200120
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Health and Social Correlates of Reincarceration Among Hispanic, Native American, and White Rural Women

Abstract: Objective To identify community reentry needs, this study examined mental illness, substance dependence, and other correlates of reincarceration in an ethnically diverse, rural population of women prisoners. Methods A purposive, cross-sectional sample of 98 women in a New Mexico state prison completed structured interviews. Analyses examined associations of substance dependence, mental illness, lifetime trauma, and sociodemographic variables with previous incarceration. Results Eighty-five percent screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Such disparities lead to social and psychological suffering (e.g., poverty, mental illness, and substance use issues). In New Mexico and elsewhere, a history of patriarchy and its ongoing effects have been implicated in the systematic devaluation of, and violence against, women-especially women of color [23,27,32]. In previous studies, we showed that women leaving prison in this environment must rely on informal and insecure networks of family and friends-many of whom also struggle with substance abuse-for financial assistance, housing, and transportation.…”
Section: Intimate Partner Violence Rurality and Incarceration Of Womenmentioning
confidence: 79%
See 1 more Smart Citation
“…Such disparities lead to social and psychological suffering (e.g., poverty, mental illness, and substance use issues). In New Mexico and elsewhere, a history of patriarchy and its ongoing effects have been implicated in the systematic devaluation of, and violence against, women-especially women of color [23,27,32]. In previous studies, we showed that women leaving prison in this environment must rely on informal and insecure networks of family and friends-many of whom also struggle with substance abuse-for financial assistance, housing, and transportation.…”
Section: Intimate Partner Violence Rurality and Incarceration Of Womenmentioning
confidence: 79%
“…Moreover, IPV continues to affect women's lives after reentry and is connected to their likelihood of recidivism [19,21]. Experiences of IPV are pervasive in the lives of incarcerated women returning to rural communities [22,23], largely due to the scarcity of supportive resources, employment opportunities, adequate and affordable housing, and the strong presence of traditional ideologies of power, patriarchy, and privacy that structure gender relationships and policing in rural states [24,25]. Studies also link racism, poverty, and patriarchy with the abuse and incarceration of women, particularly Native Americans [26][27][28].…”
Section: Intimate Partner Violence Rurality and Incarceration Of Womenmentioning
confidence: 99%
“…Participants were 20–56 years old (median=34); 51.5% completed high school or the general educational development test; 89% were mothers; 33.3% derived their income from a job 6 months prior to incarceration; and 51.5% reported economic hardship during this period, i.e., not having sufficient income to meet basic needs. As described in in a separate publication (Willging, Malcoe, St. Cyr, Zywiak, & Lapham, 2013), 85% of inmates screened positive for substance dependence, 49% positive for a serious mental illness, and 45% positive for both. All had incurred trauma, often related to childhood sexual abuse or intimate partner violence; 47% had returned to prison for new crimes or parole violations largely related to struggles with alcohol or drugs.…”
Section: Resultsmentioning
confidence: 82%
“…Criminally involved women also face significant difficulty upon re-entry due to their economic marginalization, which is marked by limited access to resources, health care, and public assistance (Lilliot et al, 2017). The difficulty that these women encounter in trying to attain these important predictors of successful reentry increases their risk of recidivating (Willging, Malcoe, St. Cyr, Zywiak, & Lapham, 2013), overdosing on drugs, or committing suicide shortly following their release (Binswanger et al, 2007). Heindesohn (1985) suggested that criminologists must acknowledge the social control and marginalization of women in order to understand women and crime.…”
Section: The Criminalization Of Womenmentioning
confidence: 99%